Respect With Recognition? A Defence of the OCSTA’s “Respecting Difference” Policy - Jordan, Michael Robert (Philosophical Inquiry in Education, 2016)
Philosopher Lauren Bialystok argues that some of the ideas within Ontario’s Catholic trustees’ document entitled ‘Respecting Difference’ fail to respect homosexual Catholic schoolchildren. I argue that Bialystok’s argument is unsuccessful because she begs at least three questions.